Nanotechnology in the perioperative treatment of head and neck cancer: application and outlook - Zhou, Jun-Jie; Feng, Yan-Chuan; Zhao, Min-Long; Guo, Qi; Zhao, Xi-Bo (Frontiers in Bioengineering and Biotechnology, 2025)
Head and neck cancer (HNC) critically affects patient survival and quality of life, highlighting the need for optimized perioperative interventions. While conventional therapies face limitations in specificity and toxicity, nanotechnology has emerged as a revolutionary approach. Preoperative application of tumor-targeting nanoprobes enables molecular-level lesion identification via biomarker-specific conjugation and spatially resolved fluorescence quantification. Intraoperatively, fluorescent nanomaterials enhance surgical precision through selective tumor accumulation, delineating malignant margins in real time. Postoperatively, engineered nanocarriers improve therapeutic outcomes by delivering drugs with spatial control, minimizing off-target effects, and enabling multimodal synergies. These nanotechnology-driven strategies collectively address critical challenges in HNC management, including diagnostic sensitivity, intraoperative visualization, and postoperative recurrence. Their inherent advantages—precision targeting, reduced systemic toxicity, and multifunctional integration—establish them as cornerstone tools in modern oncology. Future advancements in nanomaterial design and biocompatibility are poised to further refine therapeutic efficacy, survival rates, and patient-centered outcomes.